Mechanically improved antibacterial polycaprolactone/propolis electrospun fiber mat by adding bacterial nanocellulose - Sutjarittangtham K. (American Scientific Publishers, 2015)
Copyright © 2015 American Scientific Publishers All rights reserved. This work describes the preparation of polycaprolactone (PCL) fibers added propolis by electrospinning a polymer solution in glacial acetic acid. Fibers were collected on a rotating drum to make a fiber mat. But the propolis have the effect on mechanical properties of the fiber mat, therefore the fiber mat mechanical properties were improved by adding nanocellulose from 0-3%w/v. The morphology of the fiber mat was observed by a scanning electron microscope (SEM). It can be seen that the fiber diameter decreased with added nanocellulose also a few beads were observed for the propolis added sample. The mechanical properties of the fiber mat were measured using a universal tensile tester, the maximum tensile stress (σm ), elongation at break (εb ) and Young's elastic modulus (E) were obtained. Mechanical characterization indicated that nanocellulose significantly improved the mechanical properties with maximum tensile strength more than doubled. However, the composite containing propolis shows good antibacterial activity. The molecular composition of the fiber mat was investigated by Fourier transform infrared analysis (FT-IR).